Interferon Alpha Induces Cellular Autophagy and Modulates Hepatitis B Virus Replication - Li, Jia; Kemper, Thekla; Broering, Ruth; Chen, Jieliang; Yuan, Zhenghong; Wang, Xueyu; Lu, Mengji (Frontiers in Cellular and Infection Microbiology, 2022)
Hepatitis B virus (HBV) infection causes acute and chronic liver diseases, including severe hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). Interferon alpha 2a (IFNα-2a) is commonly used for treating chronic HBV infection. However, its efficacy remains relatively low. Yet, the immunological and molecular mechanisms for successful IFNα-2a treatment remain elusive. One issue is whether the application of increasing IFNα doses may modulate cellular processes and HBV replication in hepatic cells. In the present study, we focused on the interaction of IFNα signaling with other cellular signaling pathways and the consequence for HBV replication. The results showed that with the concentration of 6000 U/ml IFNα-2a treatment downregulated the activity of not only the Akt/mTOR signaling but also the AMPK signaling. Additionally, IFNα-2a treatment increased the formation of the autophagosomes by blocking autophagic degradation. Furthermore, IFNα-2a treatment inhibited the Akt/mTOR signaling and initiated autophagy under low and high glucose concentrations. In reverse, inhibition of autophagy using 3-methyladenine (3-MA) and glucose concentrations influenced the expression of IFNα-2a-induced ISG15 and IFITM1. Despite of ISGs induction, HBV replication and gene expression in HepG2.2.15 cells, a cell model with continuous HBV replication, were slightly increased at high doses of IFNα-2a. In conclusion, our study indicates that IFNα-2a treatment may interfere with multiple intracellular signaling pathways, facilitate autophagy initiation, and block autophagic degradation, thereby resulting in slightly enhanced HBV replication.